Maintenance of Membrane Fluidity during Development of Freezing Tolerance of Winter Wheat Seedlings - Pomeroy, M. Keith (1981)
Fluidity of membrane lipids of shoot and root tissue and of chloroplasts from young wheat seedlings of contrasting freezing tolerance was investigated by measuring the motion and order parameters after spin labeling. A striking similarity was observed in membrane lipid fluidity of the five cultivars grown at 22 C. After cold hardening by growth at 2 C, a small change in membrane lipid fluidity was observed, but this was not correlated with the development of freezing tolerance, and there was no alteration in the transition temperature of membrane lipids. The results show that neither changes in membrane lipid fluidity nor transition temperature are a necessary feature of cold acclimation in wheat.